ANALISIS KAUSALITAS ANTARA KORUPSI DAN PEMBANGUNAN BERKELANJUTAN DI ASIA TENGGARA - Rifki Khoirudin (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The purpose of this study is to ascertain the causal link between corruption and sustainable development. The Corruption Perception Index (CPI), Human Development Index (HDI), Carbon Dioxide Emissions (CO2), and Foreign Direct Investment (FDI) variables were used in this study. The data for this analysis were derived from secondary sources such as the World Bank, the United Nations Development Programme, and Transparency International. The stationary test, cointegration test, optimum lag test, and Granger causality test were all employed in this study. The study's findings indicate that corruption and sustainable development are causally related. Corruption and sustainable development have a two-way causative link from a socioeconomic viewpoint, a one-way causal relationship from an environmental perspective, and a one-way causation relationship between corruption and foreign direct investment. Corruption has proven to be an obstacle to the sustainable development of every country.